Role of Topical Heparin in the prevention of Super?cial Thrombophlebitis - Lata D Shetty; Bhagyashree C Bagodi; Bahubali Gane (Academia Anesthesiologica International, 2020)
Background: Sometimes the use of an intravenous (IV) catheter is associated with superficial thrombophlebitis. The efficacy of the topical Heparin solution was compared with placebo for the prevention of thrombophlebitis related to IV catheter. Subjects and Methods : Patients who were 18-45 years of age with an intravenous catheter for at least 72 h were registered and randomized to receive 3-6 drops of topical solution of heparin (Group H) over the 18G catheterized vein every 8th hourly for a total of 6 doses and another group (Group N) did not receive any topical solution over 18G catheterisation. Patients enrolled were examined every 12 h for phlebitis using the phlebitis visual infusion scale. Result: Usage of the phlebitis visual infusion scale to examine phlebitis every 12 hours. In group H mean Phlebitic scale was 0.08 0.27, 0.12 0.33, 0.24 0.43, 0.28 0.45, 0.36 0.56 and 0.52 0.77 at 12, 24, 36, 48, 60 and 72 hours respectively. The mean phlebitic scale in group N was 0.60 0.50, 0.72 0.61, 1.04 0.67, 1.08 0.64, 1.16 0.55 and 1.72 0.89 respectively at 12, 24, 36, 48, 60 and 72 hours. In group H mean phlebitic scale was significantly lesser as compare to group N. Conclusion: After peripheral intravenous catheterisation, prophylactic topical application of heparin was effective in preventing the development of superficial thrombophlebitis.